EuroQoL-Visual Analog Scale as a Tool for Assessing Health Status in Breast Cancer Patients: A Cross-sectional Study - Richha Prabhakar; Rajat Prabhakar; Dharmapuri R. Rao (Journal of Mid-Life Health)
Introduction: Breast cancer significantly influences women’s health and overall well-being, necessitating comprehensive assessments to guide effective supportive care during cancer treatment. This study utilizes the EuroQoL-Visual Analog Scale (EQ-VAS) to systematically evaluate the health status and quality of life in women undergoing treatment for breast cancer. Materials and Methods: A study was conducted on a sample of 100 patients with breast cancer who were treated at a tertiary care hospital in New Delhi. The EQ-VAS, a part of the EuroQoL five-dimension instrument, was used to evaluate the participants. It measures the participants’ self-rated health on a vertical visual analog scale, with 0 representing the worst possible health and 100 representing the best health. Results: The participants’ mean EQ-VAS score was 46.95 (standard deviation = 9.4), which denotes low self-perceived health. There were notable differences in EQ-VAS ratings between the various stages of breast cancer, with advanced stages exhibiting lower scores. Patients who underwent surgery for breast cancer were reported with high EQ-VAS scores (52.00 ± 16.71). Conclusion: The results emphasize the different health experiences of women suffering from breast cancer and the value of individualized care programs during cancer care. The EQ-VAS has shown to be a valuable instrument for gathering patient self-perceived health status, providing important information for healthcare professionals to improve supportive care and the overall health of women struggling with breast cancer.